math-algebra

posted by .

how do i solve this using the substitution method

3x+2y=7
2x-3y=-4

x=7-2y/3

2(7-2y/3)-3y=-4

this is where i get stuck
help would be much apprieciated

  • math-algebra -

    3x+2y=7
    3x=-2y+7
    x=-2/3y+7/3
    2(-2/3y+7/3)-3y=-4
    -4/3y+14/3-3y=-4
    Combine like terms, solve for y, replace y in either original equation to solve for x. Post your work to get it checked.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Substitution Method-Plz help

    Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get it.How …
  2. Algebra

    Systems of equations can be solved by graphing or by using substitution or elimination. What are the pros and cons of each method?
  3. algebra

    How would you solve the systemof equations using the substitution method: 2x-9y=2 4x+18y=12
  4. algebra

    o Systems of equations can be solved by graphing or by using substitution or elimination. What are the pros and cons of each method?
  5. math - algebra

    how would i solve this using the substitution method 3y=11-x 3x-y=3 thanks
  6. Algebra

    How would you solve this using substitution method y= 3 + x 2x + y = 8
  7. Algebra 1

    Solve using two different methods. Explain which method you found to be most efficient. A. 3x - 9y = 3 6x - 3y = -24 B. 7x - 3y = 20 5x + 3y = 16 C. y = 1/2x - 6 2x + 6y = 19 I am just stuck and don't know how to do these last few …
  8. Algebra 1

    bobpursey, In this problem you helped me with earlier: Solve using any appropriate method. y = 2× - 5, y = ½× + 1 Substitution, substitute for y. 2×-5=½ × + 1 3/2 x=6 x=4 y= 2*4-5=3 How did you choose which method you were going …
  9. Algebra

    solve using substitution method: 4x+5y=21 x=48-6y
  10. Math

    17) solve this linear system using the method of substitution. 2y-x=-10 y= -3/2x-1 20) simplify then solve by substitution 2(x-4)+y=6 3x-2(y-3)=13 just need help with these 2.

More Similar Questions